Wintering ecology and nomadic movement patterns of Short-eared Owls Asio flammeus on a subtropical island. Issue 3 (3rd July 2017) - Tseng, Wei; Lin, Wen-Loung; Lin, Si-Min
ABSTRACT: Capsule: Short-eared Owls Asio flammeus showed a female-biased sex ratio in their southernmost wintering grounds in Oriental Asia. This is the first description of a nomadic movement pattern in this area. Aims: To investigate the sex ratio, movement patterns, home range size and habitat preference of non-breeding Short-eared Owls in subtropical Taiwan. Methods: Eleven Short-eared Owls were radio tracked following trapping and transportation away from an airport as part of the management of bird-strike risk for aeroplanes. Results: Our results indicated a female-skewed (75%) sex ratio for Short-eared Owls wintering in Taiwan. The owls demonstrated a nomadic behaviour by showing a repetitive pattern of high roosting site fidelity in the short term, followed by a long-distance movement to a different discrete area. Grasslands were commonly used as day-roosting sites but agricultural habitats were favoured at night. Conclusion: Compared to on the breeding ground, the wintering owls exhibited a much larger home range size and exploit more dispersed patches of suitable habitats. These results revealed a notable conservation issue for the wintering owls, especially in the degraded and partially developed landscapes in subtropical countries.